Continual reproduction of self-assembling oligotriazole peptide nanomaterials - Roberto J. Brea (Nature Portfolio, 2017)
Molecules that act as both autocatalysts and material precursors offer exciting prospects for self-synthesizing materials. Here, the authors design a triazole peptide that self-replicates and then self-assembles into nanostructures, coupling autocatalytic and assembly pathways to realize a reproducing supramolecular system.